Translational profiling of adipocytes within adipose depots and intermuscular adipose tissues - Hassan, Sara Serag (AUC Knowledge Fountain, 2017)
The imbalance between energy intake and energy expenditure elicited a worldwide problem, which is obesity. Obesity is associated with wide array of medical disorders not only limited to cardiovascular diseases, but also extended to include immune disorders, as well as some types of cancer. Hence, there is an indispensible need for identifying new therapies for tackling this serious health burden. The pathophysiological aspects of obesity include the storage of excess energy as fat droplets in adipocytes within adipose depots. Another less studied aspect of obesity is the increased fat storage ectopically in other organs such as skeletal muscle, liver, pancreas, bone marrow and heart. In this study, we performed an adipocyte-specific RNAseq using a translating ribosomal affinity purification (TRAP) by crossing the transgenic TRAP mice with Adiponectin-Cre mice where Adiponectin is a mature fat cell protein. Using this approach, we have selectively isolated polysomes from Adiponectin-positive cells from brown, subcutaneous, visceral adipose depots and quadriceps muscle in mice. Using differential gene expression analysis (DEseq), we identified S100B as a BAT enriched protein whose role in fat metabolism has not been elucidated before. Here, we describe the role of S100B in inducing thermogenesis through activating lipolysis pathways. In vivo studies using overexpression adenovirus systems showed that S100B improved obesity-induced glucose intolerance and enhanced respiration capacity of mice. Moreover, loss of function experiments demonstrated a physiological role of S100B in stimulating lipolysis and ultimately in activating thermogenesis. We also applied the TRAP model for characterizing the transcriptomic make up of inter/intra-muscular adipose tissue (iMAT). IMAT represents one of the ectopic adipose tissues linked with insulin resistance. Identifying the transcriptomic pattern of iMAT represented a major challenge owing to their location. We demonstrate the close relationship between iMAT and subcutaneous fat cells both in their genetic signature and their ability to respond to cold. Collectively, the TRAP approach is a powerful tool for characterizing transcripts of mature adipocytes that can be utilized for discovering new regulators of adipose tissues. In addition, it can be used for deciphering other ectopically embedded adipocytes within organs such as the heart, pancreas and bone marrow.